MASTERING TEST-TAKING READING SKILLS WITH CONTEXTUAL GUESSING: THE CASE OF UNIFIED ENTRANCE EXAM - Olha Chaikovska; Alla Bodnar; Valentyna Spivachuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2022)
A high percentage of bachelor test-takers who failed the unified entrance examination test in 2021 demonstrated the lack of adequate reading strategies such as contextual guessing for improving exam performance. The study aims at evaluating the use of contextual guessing strategy during extra-curriculum EFL classes as a way to improve students' unified entrance examination performance. The present study also examines the impact of word formation as a component of contextual guessing strategy and the effectiveness of contextual guessing with online vocabulary application in exam preparation. A quasi-experimental design was employed which involved 24 third-year students from different departments of Higher Educational Institution "Podillia State University" in 2020-2021. The quantitative research method was employed to assess the effectiveness of using contextual guessing to improve students' test performance using the mean score formula. Additionally, we produced a test statistic based on the ranks (Mann-Whitney U-criterion). The results showed that the experimental group that was taught the strategy of guessing unknown words with the help of word-formation processes, and contextual clues, in particular, and applied the vocabulary platform for fixing and retaining guessed words had higher results than those who were taught unified entrance examination tests with the help of the grammar-translation method. Based on Mann-Whitney U-criterion we have statistically significant evidence to conclude that contextual guessing significantly affects EFL learners' test performance in experimental and control groups. The guide on word formation was designed during the experiment.